AI-enhanced education: bridging educational disparities - Ahmed, Zeinab E; Hassan Abdalla Hashim, Aisha; Saeed, Rashid A; Saeed, Mamoon M A (IGI Global, 2024)
This chapter explores the symbiotic relationship between AI and education, highlighting its transformative impact and potential to bridge educational disparities. It provides insights into using AI to create engaging and efficient learning environments, covering various topics such as AI-driven teaching techniques, ethical considerations, and case studies. AI tools enhance learning experiences and help address disparities among students. The integration of AI in education can optimize resources, personalize learning, and improve academic performance. However, challenges such as lack of familiarity and technical difficulties need to be addressed through training and support for teachers. By embracing AI, educators can revolutionize teaching methods and promote equity and inclusivity in education.